2019
DOI: 10.3389/fnhum.2019.00113
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Object Location in Augmented Reality: The Role of Gender and the Relationship Among Spatial and Anxiety Outcomes

Abstract: The potential of augmented reality (AR) technology for the study of spatial memory and orientation is a new research field. AR defines systems that attempt to enhance the user’s experience with the physical world. In our app, we enhance the sense of sight by adding interactive 3D elements to the real environment. Our app can be used in any real environment so that the experimental conditions during the tasks and the way in which an individual navigates are similar to those used in real life. With AR, the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 64 publications
3
25
0
1
Order By: Relevance
“…Our research group has presented most of these works. Our group has pioneered the development and validation of AR applications for the assessment of spatial memory [20,[29][30][31]. In the first work [20,29], we developed an AR application that used image targets that were distributed in the real world.…”
Section: Assessment Of Spatial Memory Using Virtual and Augmented Realitymentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has presented most of these works. Our group has pioneered the development and validation of AR applications for the assessment of spatial memory [20,[29][30][31]. In the first work [20,29], we developed an AR application that used image targets that were distributed in the real world.…”
Section: Assessment Of Spatial Memory Using Virtual and Augmented Realitymentioning
confidence: 99%
“…In the first work [20,29], we developed an AR application that used image targets that were distributed in the real world. In the second work [30,31], we presented an AR application based on SLAM for visual stimuli. The main difference with the previous work was that no additional elements were added to the real environment.…”
Section: Assessment Of Spatial Memory Using Virtual and Augmented Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that, generally speaking, males perform better than females in visuo-spatial working memory tasks ( Cornoldi & Vecchi, 2004 ). However, one study has demonstrated that, although males performed better than females on a paper-andpencil task assessing object-location memory, no differences were observed on an augmented reality task assessing this type of memory ( Munoz-Montoya et al, 2019 ). Also, the participants’ performance in this study was significantly correlated with anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Munoz et al [19] demostraron que recorrer el entorno y ver los objetos virtuales en el mundo real ayuda a los participantes a recordar la ubicación de los objetos virtuales en el entorno real si se compara con ver fotografías del entorno aumentado. Nuestra propuesta comparte la misma idea de que los estímulos a utilizar deben estar ubicados en el entorno real [19] [20]. En…”
Section: Evaluación De La Memoria Espacialunclassified